KONSENTRASI LARUTAN GARAM PADA FERMENTASI KULIT BUAH CEMPEDAK (Artocarpus integer) TERHADAP SIFAT FISIK, ORGANOLEPTIK DAN KADAR VITAMIN C MANDAI - Nadya Desanti Hartiningtyas; Agus Wijanarka; Siska Puspitasari (Jurnal GIZIDO, 2020)
Background: Cempedak is a fruit that is one of Indonesia’s native plants. Cempedak fruit containsa lot of water amount up as much as 67% which makes the fruit easily rotten and can not be stored for a long period of time. In Kalimantan, people often process cempedak as a traditional food called mandai. Mandai fermentation process is part of the efforts to preserve food to be available for a long time as well as an efforts to use waste from the consumption of cempedak fruit. Method: This type of research is a pure experiment with several treatments. In this research,several variables were used to examine the physical properties, organoleptic properties and vitamin C level. The experimental design provided is thr Complete Randomized Design (CRD) with one unit of experiment, 3 treatment variations and 3 repetitions. With the use of salt solution concentrations of 5%, 10% and 15%. Results: The results stated that the concentration of salt solution had an effect on the physicalproperties of the mandai, thus are in color, aroma, taste and texture. The results of organoleptic research stated that there is an effect of the concentration of salt solution on the cempedak skin on the level of color preference, aroma, taste, texture and overall the mandai with the most preferred salt solution concentration level, is the mandai with 5% salt solution. There is no effect of the concentration of salt solution on the cempedak skin on the vitamin C levels. Conclusion: There is an influence on the physical and organoleptic properties of mandai and thereis no effect of the salt solution concentration on mandai vitamin C levels.